Enantioselective Copper-Catalyzed Alkynylation of Benzopyranyl Oxo-carbenium Ions - Srinivas, Harathi D. (J Org Chem, 2015)
We have developed highly enantioselective, copper-catalyzed alkynylations of benzopyranyl acetals. By using a copper(I) catalyst equipped with a chiral bis(oxazoline) ligand, high yields and enantioselectivities are achieved in the alkynylation of widely available, racemic isochroman and chromene acetals to deliver α-chiral oxygen heterocycles. This method demonstrates that chiral organometallic nucleophiles can be successfully used in enantioselective additions to oxocarbenium ions.